The Effect of Project-Based Learning Model (PjBL) with STEM Approach to Promote Students' Critical and Creative Thinking Skills: A Meta Analysis - Feziyasti, Azifa; Saputri, Indah; Asrizal, Asrizal; Mufit, Fatni (Radiasi : Jurnal Berkala Pendidikan Fisika, 2025)
Critical and creative thinking skills are essential 21st century competencies needed to prepare students for global challenges and an evolving workforce. Despite their importance, the 2018 PISA results indicate that Indonesian students still exhibit low critical thinking skills, underscoring the need for more effective learning approaches. This take a look at goals to investigate the effect of the STEM-based Project-Based Learning (PjBL) model on critical and creative thinking skills through a meta-analytic approach. The analysis included 20 articles published between 2018 and 2024, covering two variables: subject domains and learning materials. The findings discovered that STEM-based PjBL had a big impact, with excessive average impact sizes for essential questioning abilities, in particular in dynamic fluid topics, and for creative wondering talents in biodiversity subjects. PjBL combined with the STEM method effectively enhances students' analytical, communication, and collaboration skills through active engagement in real-world problem-solving. Therefore, the STEM-based PjBL model is a relevant approach to fostering critical and creative thinking skills in 21st-century education.